415. Epidemiological Evaluation of Antibiotic Resistance and Subsequent Effect on Healthcare Resource Utilization among Subjects with Pseudomonas aeruginosa Infections in Italy. (15th December 2022) - Bassetti, Matteo; Cascio, Antonio; Cattelan, Annamaria; Cauda, Roberto; Menichetti, Francesco; Petrosillo, Nicola; Rescigno, Carolina; Tascini, Carlo; Vena, Antonio; Viale, Pierluigi
Abstract: Background: The aims of the study were to 1) evaluate the prevalence of multidrug resistant (MDR) /Extensively drug resistant (XDR) strains among hospitalized adults with Pseudomonas aeruginosa ( PA ) infections, and 2) examine whether antimicrobial resistance in PA infections is associated with worsening functional status and higher health care resource utilization (HCRU). Methods: This multicenter prospective study was conducted in 9 large Italian teaching hospitals between June 2018-February 2020. We included patients aged ≥18 years with a diagnosis of nosocomial pneumonia (NP), complicated urinary tract infections (cUTI) or complicated intra-abdominal infections (cIAI) due to PA as confirmed by local evaluation of microbiological results. MDR PA was defined as acquired non-susceptibility to at least one agent in three or more antimicrobial categories. XDR PA was defined as acquired non-susceptibility to at least one agent in all but two or fewer antimicrobial categories. HCRU metrics evaluated included hospital length of stay (LOS) and intensive care unit (ICU) LOS. Results: A total of 95 patients with a nosocomial infection due to PA were enrolled. The main baseline characteristics of overall patients were reported in Table 1. Almost one-third of patients (28.4%) reported either MDR or XDR PA infection, with more patients experiencing MDR (Table 1). Health care resource use stratified by patients with and without MDR/XDR status are reported in Table 2. Overall, in our study population, median hospital LOS and ICU LOS were 42.0 (IQR=39.0) and 15.5 (IQR=37.0) days, respectively. There was a statistically significant longer median hospital LOS for patients with MDR/XDR infections compared to non MDR/XDR PA infections (53.0 vs. 36.5 days, p=0.04). ICU LOS also trended towards being longer for patients with MDR/XDR infections compared to those with non-MDR/XDR infections (25.5 vs. 13.5 days, p=0.10). Conclusion: MDR/XDR isolates were prevalent among patients with nosocomial infections due to PA, particularly in those with cIAI. Overall, the present study may suggest a positive correlation between having MDR-XDR PA nosocomial infections (NP, cUTI, and cIAI) and increased HCRU that require further attention from a disease management perspective. Disclosures: Matteo Bassetti, PhD, Angelini: Advisor/Consultant|Astellas: Grant/Research Support|Bayer: Advisor/Consultant|Bayer: Honoraria|BioMe ́ rieux: Advisor/Consultant|BioMe ́ rieux: Honoraria|Cidara: Advisor/Consultant|Cidara: Honoraria|Cipla: Advisor/Consultant|Cipla: Honoraria|Gilead: Advisor/Consultant|Gilead: Honoraria|Menarini: Advisor/Consultant|Menarini: Honoraria|MSD: Advisor/Consultant|MSD: Honoraria|Nabriva: Advisor/Consultant|Pfizer: Advisor/Consultant|Pfizer: Board Member|Pfizer: Grant/Research Support|Pfizer: Honoraria|Shionogi: Advisor/Consultant|Shionogi: Honoraria|Tetraphase: Advisor/Consultant Francesco Menichetti, n/a, Aneglini: Advisor/Consultant|Aneglini: Board Member|Aneglini: Grant/Research Support|Aneglini: Honoraria|Astellas: Advisor/Consultant|Astellas: Honoraria|Becton: Advisor/Consultant|Becton: Honoraria|bioMérieux: Advisor/Consultant|bioMérieux: Honoraria|Biotest: Advisor/Consultant|Biotest: Board Member|Biotest: Honoraria|Bristol-Myers Squibb: Advisor/Consultant|Bristol-Myers Squibb: Honoraria|Correvio: Advisor/Consultant|Correvio: Speaker honoraria|Dickinson: Advisor/Consultant|Dickinson: Honoraria|Gilead: Advisor/Consultant|Gilead: Grant/Research Support|Janssen: Advisor/Consultant|Janssen: Honoraria|MSD: Advisor/Consultant|MSD: Speaker honoraria|Nordic pharma: Board Member|Nordic pharma: Honoraria|Pfizer: Advisor/Consultant|Pfizer: Honoraria|Shionogi: Advisor/Consultant|Shionogi: Honoraria|ViiV: Advisor/Consultant|ViiV: Honoraria Nicola Petrosillo, n/a, Becton & Dickinson, : Honoraria|MSD: Honoraria|ohnson & Johnson: Honoraria|Pfizer: Honoraria|Shionogi: Honoraria.